2007
DOI: 10.1007/s00213-006-0627-5
|View full text |Cite
|
Sign up to set email alerts
|

Delay discounting predicts cigarette smoking in a laboratory model of abstinence reinforcement

Abstract: The patch did not attenuate delay discounting or smoking after a period of deprivation, but contingencies for abstinence significantly decreased smoking. Higher rates of delay discounting were related to smoking in a model of abstinence reinforcement treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
2
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(125 citation statements)
references
References 63 publications
7
110
2
6
Order By: Relevance
“…Some authors refer to the tendencies of subjects to conceptualize delay discounting. Importantly, however, although individuals may differ with regard to delay discounting in the form or degree to which the delayed results depreciate, delay discounting must be considered as a behavioral tendency that can change under different environmental or pharmacological conditions rather than as a fixed trait (Dallery & Raiff, 2007).…”
Section: Decision-making and Delay Discountingmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors refer to the tendencies of subjects to conceptualize delay discounting. Importantly, however, although individuals may differ with regard to delay discounting in the form or degree to which the delayed results depreciate, delay discounting must be considered as a behavioral tendency that can change under different environmental or pharmacological conditions rather than as a fixed trait (Dallery & Raiff, 2007).…”
Section: Decision-making and Delay Discountingmentioning
confidence: 99%
“…Indeed, as mentioned previously, they are anomalies only when considering normative models that are constructed without considering descriptive validity (Frederick et al, 2002;Rachlin, 2007). Anomalies are present in a large number of studies (Chapman & Elstein, 1995;Dallery & Raiff, 2007;Estle, Green et al, 2006;Johnson et al, 2007;Kirby et al, 1999), and their best function is to provide information about delay discounting, the variables for which this phenomenon is a function, the task itself, and the choice behavior of human and nonhuman subjects. Some studies have shown that the stability of the task is limited by factors identified throughout time, a demonstration that occurs as a type of bonus associated with the greatest choice and delay.…”
Section: Anomaliesmentioning
confidence: 99%
See 1 more Smart Citation
“…It also has generated evidencebased practices in health care and related disciplines such as clinical psychology [81], substance abuse [82,83], education [29], medicine [4], neuropsychology [30], developmental disabilities [27], and occupational therapy [84]. Although different methods are required for different purposes, SCDs are ideally suited to optimize interventions, from development to dissemination.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies such as Bickel et al (1999), Reynolds (2004), Dallery and Raiff (2007), and Ohmura et al However, we have reasons for not using either of these approaches. Evaluation of the degree of hyperbolic discounting by estimation of the hyperbolic function is limited in that it assumes a specific functional form.…”
Section: Estimation Methodsmentioning
confidence: 95%